(untitled) (Environment & Health, 2026)
The aim. To substantiate and systematize an integrated model for the prevention of hyperprolactinemia in women with metabolic syndrome. Materials and methods. The study involved 203 women of reproductive age from 20 to 49 years, who were verified to have metabolic syndrome. All patients underwent laboratory and clinical examination with determination of prolactin, total cholesterol, glucose, Noma index, leptin. The hardware examination was performed using magnetic resonance tomography. The analysis of the study results was performed using IBM SPSS Statistics version 26 software. Results. A comprehensive prevention system is proposed, including lifestyle modification, psychoemotional stabilization, correction of metabolic disorders, pharmacological and educational interventions. Conclusions. An integrated approach allows you to influence all pathogenetic links in the formation of metabolic syndrome. The most effective is a combination of non-drug and pharmacological measures. Psycho-emotional correction is a necessary component of prevention.